Maintaining Hope in Transition: A Theoretical Framework to Interventions for People with Heart Failure - Davidson, Patricia; Dracup, K.; Phillips, J.; Padilla, G.; Daly, J. (Lippincott Williams and Wilkins, 2007)
Theoretical frameworks provide a structure for the planning and delivery of nursing care and for research. Heart failure (HF), a condition of increasing prevalence in communities internationally, is responsible for high rates of morbidity, mortality, and great societal burden. The HF illness trajectory can be unpredictable and uncertain. Markers of transition, such as functional decline and increasing dependence, can signal the need for transition to a more palliative approach. This transition challenges clinicians to deliver information and interventions and to support patients and their families not only in relation to their physical status but also in the social, psychological, and existential dimensions. This article describes a theoretical framework, Maintaining Hope in Transition, informed by transition theory, to assist patients to cope with a diagnosis of HF and to guide development of nursing interventions. Transition theory provides a useful context to assist clinicians, patients, and their families adjust to the challenges inherent in a diagnosis of HF and negotiating the illness trajectory. Key factors acknowledged in the Maintaining Hope in Transition framework that determine its utility in models of care for HF patients are (1) acknowledging the changing of life circumstances, (2) restructuring reality, (3) dealing with vulnerability, (4) achieving normalization, and (5) resolving uncertainty. It is likely that incorporation of these factors in care planning, information, and interventions can facilitate patients’ and their families’ abilities to negotiate the HF illness trajectory, particularly in the advanced stages.